Boldly Explore: Camille Flammarion (1888) - Magruder, Kerry; Magruder, Susanna (My University, 2015)
Science is a quest of discovery, the challenge of boldly exploring where no one has gone before. That is the appeal and rhetorically durable theme which has made this woodcut so appealing. Many have reprinted this illustration through the years, sometimes without knowing its original source. It first appeared in this popular work on meteorology. Flammarion was an astronomer and popular science writer who worked at the Juvissy Observatory in Paris. He was mistaken in his belief that scientists, writers and theologians in the Middle Ages and Renaissance regarded the Earth as flat. This OER includes a newly colorized version of Flammarion's image by Susanna Magruder.
Keywords: Galileo's World; History of Science; Iconic Images; meteorology